Implementation of Halal Certification as an Effort to Protect Consumers and UMKM - Zainudin; Rismana, Daud; Permonoputri, Rifi Maria Laila Fitri; Widyastuti, Reza; Hariz, Hajar Salamah Salsabila (Indonesian Academy of Social and Religious Research (IASRR), 2024)
There are still products in the process of issuing halal certificates, even though numerous goods circulating in society promise halalness until 2024. Consequently, comprehensive provisions are required to cover goods and services. This follows the regulations explicitly regulated in Law Number 6 of 2023, Law Number 33 of 2014, and Article 4 of Law Number 8 of 1999 about consumer protection. This writing employs normative juridical legal and field research methods to observe and collect data from real-world societal situations to obtain the necessary facts. The study's findings show that the halal certification program has been effectively implemented in Indonesia's national legal framework, as outlined in Law Number 6 of 2023, Law Number 33 of 2014 concerning Halal Guarantee Products, and Law Number 8 of 1999 concerning Consumer Protection. The government's efforts to enhance the halal certification program are demonstrated by the self-declare program and halal certification assistance in socialization and data collection for halal certification registration, facilitating business actors to obtain halal certificates that enhance consumer comfort.